2005
DOI: 10.1002/ptr.1689
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of hepatitis B virus by an aqueous extract ofAgrimonia eupatoria L.

Abstract: Inhibition of HBsAg release against hepatitis B virus (HBV) was investigated in an aqueous extract prepared from the aerial parts (stems and leaves) of Agrimonia eupatoria. The inhibitory effect on HBsAg secretion was footed using aqueous extracts of Agrimonia eupatoria at four different temperatures (37 degrees C 45 degrees C, 55 degrees C and 60 degrees C), and the extract prepared at 60 degrees C was found to have the greatest effect. The inhibitory activity of Agrimonia eupatoria extracts on HBsAg secretio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 15 publications
0
22
0
1
Order By: Relevance
“…Later studies have reported the inhibitory effects of medicinal plants extracts on the replication of several viruses. Particularly herpes simplex virus type 2 (HSV-2) (Debiaggi et al, 1988), HIV (Asres and Bucar, 2005;Vermani and Garg, 2002), hepatitis B virus (HBV) Kwon et al, 2005), and emerging viral infections associated with poxvirus and severe acute respiratory syndrome (SARS) virus (Kotwal et al, 2005) were strongly inhibited by various plants extracts. Most of these studies have utilized either water soluble or alcoholic extracts of medicinal plants, and limited efforts have been directed toward the identification of active natural ingredient exhibiting antiviral effects.…”
Section: Introductionmentioning
confidence: 99%
“…Later studies have reported the inhibitory effects of medicinal plants extracts on the replication of several viruses. Particularly herpes simplex virus type 2 (HSV-2) (Debiaggi et al, 1988), HIV (Asres and Bucar, 2005;Vermani and Garg, 2002), hepatitis B virus (HBV) Kwon et al, 2005), and emerging viral infections associated with poxvirus and severe acute respiratory syndrome (SARS) virus (Kotwal et al, 2005) were strongly inhibited by various plants extracts. Most of these studies have utilized either water soluble or alcoholic extracts of medicinal plants, and limited efforts have been directed toward the identification of active natural ingredient exhibiting antiviral effects.…”
Section: Introductionmentioning
confidence: 99%
“…There are several reports in the literature indicating that agrimony has pharmacological properties as an antioxidant, antibacterial, antihepatitis B virus, and antidiabetic. [8][9][10][11][12][13] Studies on the chemical constituents of A. eupatoria have been confined to the flavonoids, phenolic acids, triterpenes, and tannins. 9,12) The EtOAc and n-BuOH fractions of the methanolic extract of A. eupatoria in the present study led to the isolation of a new flavonoid (1), together with nine known flavonoids (Fig.…”
mentioning
confidence: 99%
“…Thus, antioxidant activity has been also evaluated in our study together with investigation of cholinesterases inhibition abilities. Previous scientific investigations focused on research of the most common Agrimonia eupatoria (Gray & Flatt 1998;Kwon et al 2005). In the methanolic extract of A. eupatoria were found flavonoids with a neuroprotective effect (Lee et al 2010).…”
Section: Introductionmentioning
confidence: 98%
“…The Agrimonia species have been reported to possess several biological activities, such as antioxidant, anti-inflammatory, antiviral, antibacterial, anti-diabetic and diuretic (Copland et al 2003;Kwon et al 2005). Decoction can be used in traditional medicine for the treatment of diabetes mellitus or coronary diseases (Gray & Flatt 1998;Correia et al 2006).…”
Section: Introductionmentioning
confidence: 99%